Numerical and experimental study of leading edge tubercles with vortex generators on NACA 4415 airfoil - Aftab, Syed Mohammed Aminuddin (2017)
Low Reynolds number flows are associated with the problems of separation bubble. The presence of separation bubble reduces the performance of the airfoil. The most commonly used devices in order to increase the performance in these Reynolds number range are Vortex Generators (VG). Recently studies have shown that implementing humpback whale Tubercle Leading Edge (TLE), also enhance the performance of the airfoil. The objective of the current work is to combine TLE and VG thereby elimination of separation bubble and increase airfoil lift to drag ratio. Initially the flow over NACA 4415 at low Reynolds number (Re) of 120,000 using Computational Fluid Dynamics (CFD) is carried out, and proper methodology for selection of turbulence model for low Re flows is also reported. Five turbulence models, were tested and it was found that γ-Reϴ sst was the best suitable Reynolds Averaged Navier Stokes (RANS) model to capture the flow physics. The main mesh requirements for utilizing y-Reϴ sst is to maintain the wall y+ <1. Throughout the thesis, structured meshing has been carried out using ICEM CFD. The established turbulence model was used to conduct CFD analysis on two Tubercle Leading Edge (TLE) designs. The designs tested are, 1. Spherical 2. Sinusoidal, the geometry is modeled using CATIA V5R21. A parametric study varying the amplitude of the tubercles is also carried out. The wavelength was kept constant at 0.25c three amplitude variations 0.025c, 0.05c and 0.075c, were modeled for both spherical and sinusoidal tubercles designs. The flow Re was set to 120,000. As the tip effects were neglected, the results are for 2.5D, only the effect of span is taken into consideration. A 3D hex grid was generated around the rectangular domain with a span of 0.5c. The results showed that spherical tubercle with 0.025c amplitude was efficient at 18°AoA, it increased the l/d ratio by 6.25%. Based on these CFD results, a modified NACA 4415 airfoil with spherical TLE was fabricated. Wind tunnel testing was carried out at Re 200,000. The results were compared with previous experimental work on NACA 4415 with straight leading edge. The results of spherical TLE showed an improvement in lift to drag ratio by 67.3% at 0°, 14% at 6°, 17.6% at 12° and the performance decrement at 18° by 3.23%. This proves that spherical TLE do improve the performance but Re number effect is an important aspect which needs to be studied. Finally a CFD analysis combining spherical TLE and VG is studied. This is the novelty of the current research is the combination of TLE and VG. The results showed that the combination enhanced the performance of clean airfoil by 8.9%. TLE and VG combination improved performance by 50% at 12º AoA as compared to merely TLE airfoil. The breakthrough finding was the working mechanism of spherical TLE which appeared similar to sub boundary layer VG. Thus the combination of TLE and VG gives a major boost in enhancing the performance of airfoil working in low Re range.